2012
DOI: 10.1002/jbmr.1670
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of bone mass and osteoclast function depend on the F-actin modulator SWAP-70

Abstract: Bone remodeling involves tightly regulated bone-resorbing osteoclasts and bone-forming osteoblasts. Determining osteoclast function is central to understanding bone diseases such as osteoporosis and osteopetrosis. Here, we report a novel function of the F-actin binding and regulatory protein SWAP-70 in osteoclast biology. F-actin ring formation, cell morphology, and bone resorption are impaired in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 55 publications
(64 reference statements)
3
49
0
Order By: Relevance
“…Interestingly, however, Def6 and Swap70 play different roles in osteoclast biology although they are highly homologous in sequences and structural domain arrangement. Swap70 does not significantly affect the differentiation of osteoclasts, but was found by Jessberger group (39) and also our group (unpublished data) to promote osteoclast resorptive function by regulating F-actin rearrangement. In this study, we revealed the inhibitory role of Def6 in osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Interestingly, however, Def6 and Swap70 play different roles in osteoclast biology although they are highly homologous in sequences and structural domain arrangement. Swap70 does not significantly affect the differentiation of osteoclasts, but was found by Jessberger group (39) and also our group (unpublished data) to promote osteoclast resorptive function by regulating F-actin rearrangement. In this study, we revealed the inhibitory role of Def6 in osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 54%
“…Swap-70 plays various roles in different cell types. In bone biology, SWAP-70 regulates osteoclast function but not differentiation (39). Previous studies show that Def6 is also expressed in myeloid cells and regulates innate immunity (40).…”
Section: Introductionmentioning
confidence: 99%
“…SWAP70 is expressed in many cell types, including mast cells (Gross et al., 2002), fibroblasts (Shinohara et al., 2002), dendritic cells (Oberbanscheidt et al., 2007), monocytes, and macrophages (Hilpelä et al., 2003). In these cells, the absence of SWAP70 leads to defects in actin polymerization and impairs cell migration, adhesion, polarization, and morphology (Bahaie et al., 2012, Chopin et al., 2010, Garbe et al., 2012, Murugan et al., 2008, Ocaña-Morgner et al., 2011, Pearce et al., 2006, Ripich and Jessberger, 2011, Shinohara et al., 2002, Sivalenka and Jessberger, 2004). SWAP70 can directly bind, bundle, and stabilize actin filaments by means of its C-terminal actin binding domain (Chacón-Martínez et al., 2013, Gomez-Cambronero, 2012, Hilpelä et al., 2003, Ihara et al., 2006, Murugan et al., 2008, Pearce et al., 2011, Shinohara et al., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The prominent reduction of the CD3+ T cell population within the bone marrow of the mutant mice could be a result of intrinsic T cell defects. It is less likely to be an effect of the altered bone marrow environment, which is osteopetrotic only in Swap-70 -/- mice [22]. In contrast to SWAP-70, DEF6 is expressed in thymocytes and peripheral T cells and has been shown to be an important regulator of T cell development and homeostasis [4, 5, 23].…”
Section: Resultsmentioning
confidence: 99%
“…Since both proteins are expressed in a variety of hematopoietic cell types, and since Swap-70 -/- but not Def6 -/- mice develop mild osteopetrosis [22], some of the variations and age-dependent compensatory mechanisms described above may have been generated through interactions of the HSPCs with the mutant bone and marrow environment. Therefore we asked whether the role of SWAP-70 and DEF6 in HSC maintenance and differentiation is intrinsic to these cells.…”
Section: Resultsmentioning
confidence: 99%